Correlations between clinical, laboratory and morphological parameters of endothelial dysfunction and vascular-platelet hemostasis in patients with type 2 diabetes mellitus and hypertension with poor glycemic compensation - N. O. Pertseva (Patologìâ)
Aim. Many questions about the relationship between endothelial dysfunction and morphological substrate of hemostasis damage that occur during the progress of type 2 diabetes mellitus and arterial hypertension require clarification and further advance.